{Anti-Melanogenic Properties of Greek Plants. A Novel Depigmenting Agent from Morus alba Wood} - Chaita, Eliza; Lambrinidis, George; Cheimonidi, Christina; Agalou, Adamantia; Beis, Dimitris; Trougakos, Ioannis; Mikros, Emmanuel; Skaltsounis, Alexios-Leandros; Aligiannis, Nektarios (Molecules, 2017)
In therapeutic interventions associated with melanin hyperpigmentation, tyrosinase is regarded as a target enzyme as it catalyzes the rate-limiting steps in mammalian melanogenesis. Since many known agents have been proven to be toxic, there has been increasing impetus to identify alternative tyrosinase inhibitors, especially from natural sources. In this study, we investigated 900 extracts from Greek plants for potential tyrosinase inhibitive properties. Among the five most potent extracts, the methanol extract of Morus alba wood (MAM) demonstrated a significant reduction in intracellular tyrosinase and melanin content in B16F10 melanoma cells. Bioassay-guided isolation led to the acquisition of twelve compounds: oxyresveratrol (1), kuwanon C (2), mulberroside A (3), resorcinol (4), dihydrooxyresveratol (5), trans-dihydromorin (6), 2,4,3′-trihydroxydihydrostilbene (7), kuwanon H (8), 2,4-dihydroxybenzaldehyde (9), morusin (10), moracin M (11) and kuwanon G (12). Among these, 2,4,3′-trihydroxydihydrostilbene (7) is isolated for the first time from Morus alba and constitutes a novel potent tyrosinase inhibitor (IC50 0.8 ± 0.15). We report here for the first time dihydrooxyresveratrol (5) as a potent natural tyrosinase inhibitor (IC50 0.3 ± 0.05). Computational docking analysis indicated the binding modes of six tyrosinase inhibitors with the aminoacids of the active centre of tyrosinase. Finally, we found both MAM extract and compounds 1, 6 and 7 to significantly suppress in vivo melanogenesis during zebrafish embryogenesis.
Keywords: 2; 3′-trihydroxydihydrostilbene; 4; B16F10 melanoma cells; Computational docking analysis; Dihydroxyresveratrol; Greek flora; Melanogenesis; Morus alba; Tyrosinase inhibition; Zebrafish